2020
DOI: 10.1371/journal.pone.0238071
|View full text |Cite
|
Sign up to set email alerts
|

Research data sharing in the Australian national science agency: Understanding the relative importance of organisational, disciplinary and domain-specific influences

Abstract: This study delineates the relative importance of organisational, research discipline and application domain factors in influencing researchers' data sharing practices in Australia's national scientific and industrial research agency. We surveyed 354 researchers and found that the number of data deposits made by researchers were related to the openness of the data culture and the contractual inhibitors experienced by researchers. Multi-level modelling revealed that organisational unit membership explained 10%, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 40 publications
0
6
0
Order By: Relevance
“…Social Sciences Survey (481), interviews (234), observations (113), qualitative (98), transcripts (52), quantitative (44), audio (38), video (36), recordings (34), experimental (34) Arts and Humanities Survey (60), observations (43), texts (37), images (33), interviews (33), video (28), audio (26), qualitative (24), literary (23), historical (22) Business and Economics Survey (345), secondary (83), interviews (67), observations (31), qualitative (26), experimental (18), financial (16), quantitative (16), economic (15), time series (14) Environmental Sciences Survey (105), samples (54), observations (48), water (35), field data (30), experimental (29), measurements (23), images (22), soil (22), species (19) Earth & Planetary Sciences Models (40), Observations (32), Samples (25), Survey (25), Measurements (24), Water (17), Field data (16), Numerical (16), Chemical (15), Temperature (12) Biomedical Sciences Survey (45), images (32), behavioral…”
Section: Data Availability Statementmentioning
confidence: 99%
“…Social Sciences Survey (481), interviews (234), observations (113), qualitative (98), transcripts (52), quantitative (44), audio (38), video (36), recordings (34), experimental (34) Arts and Humanities Survey (60), observations (43), texts (37), images (33), interviews (33), video (28), audio (26), qualitative (24), literary (23), historical (22) Business and Economics Survey (345), secondary (83), interviews (67), observations (31), qualitative (26), experimental (18), financial (16), quantitative (16), economic (15), time series (14) Environmental Sciences Survey (105), samples (54), observations (48), water (35), field data (30), experimental (29), measurements (23), images (22), soil (22), species (19) Earth & Planetary Sciences Models (40), Observations (32), Samples (25), Survey (25), Measurements (24), Water (17), Field data (16), Numerical (16), Chemical (15), Temperature (12) Biomedical Sciences Survey (45), images (32), behavioral…”
Section: Data Availability Statementmentioning
confidence: 99%
“…As a result, their motivation level is low and their performance is correspondingly reduced. According to Mason et al (2020), employees perform well when they are provided with external financial rewards. Therefore, a high level of involvement within an organisational culture does not necessarily prove to be a positive influence on organisational performance.…”
Section: Discussionmentioning
confidence: 99%
“…Along with this, it is also argued that extent of organisational culture effectiveness depends on geographical location of the firm, too. Mason et al (2020) examined the relationship between organisational culture and business performance in terms of geographical location. They found that a high degree of involvement resulted in enhancing the effectiveness of organisational culture and improved performance in the context of firms operating in Thailand.…”
Section: Theoretical Framework and Hypothesesmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, those policy play important roles to ensure the rigorous of research through evaluate the methodology by using the dataset (Read et al, 2021). Research related to data sharing in the context of institutional policies through involving all stakeholders within the research ecosystem needs to be carried out as recommended from previous research in order to find the most optimum for data sharing governance (Mason et al, 2020;Zenk-Möltgen et al, 2018). The success in implementing the data sharing policy is a collective work among the stakeholders, both funding agency, researchers as the main actors in research activities, and research institutions that provide infrastructure and data services in the practice of sharing research data.…”
Section: Previous Findingsmentioning
confidence: 99%